Effective project monitoring for ERP implementation success: A case study in a S&M company in Vietnam - Đạo, Lê Đức; Khanh, Trần Xuân (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2023)
This research paper shed a light on the challenges faced during the implementation of an Enterprise Resource Planning (ERP) system in an organization, with a specific focus on project management and project monitoring. This paper also presents a case study of a company in Vietnam that experienced difficulties during the go-live phase of their ERP implementation due to poor project monitoring. The objective of the research is to identify these challenges and propose a solution to resolve the ineffective project monitoring. By doing that, the paper highlights the importance of effective project monitoring in ensuring the success of ERP implementation projects. The results of implementing the proposed solution are promising, as demonstrated by a reduction in completion time, elimination of late delivery days, and effective management of resource deviation. These outcomes illustrate the potential for improving project efficiency, reducing costs, and ensuring successful ERP system implementation. Overall, this research provides valuable insights and best practices for organizations embarking on ERP system implementations, offering guidance on overcoming challenges and achieving a smooth and successful go-live phase.